The Analysis Studies of Causes and Frequencies of Reoperations after Endoprosthesis Reconstructions for Extremity Tumor Surgery: A Comprehensive Systematic Review - Jatniko Fadhilah; Amarvir Singh (The International Journal of Medical Science and Health Research, 2024)
Introduction: Recent advancements in endoprosthetic implant designs and fixation methods have greatly enhanced the options available for reconstructing osseous defects following tumor excision. Endoprosthetic reconstruction offers multiple benefits, including versatility, improved ambulatory function, and early rehabilitation, while allowing for complete tumor resection and reducing the risk of recurrence. This systematic review aims to aggregate evidence on the complications and outcomes of primary extremity tumor endoprosthetic reconstructions to guide clinical decision-making. Methods: This review follows the PRISMA 2020 guidelines, analyzing studies published between 2004 and 2024 that address complications like infection, structural failure, and prosthesis survival in primary extremity tumor endoprosthetic reconstructions. A comprehensive search strategy across databases like PubMed, ScienceDirect, and Cochrane Library will identify eligible studies. Results: Eight studies meeting the inclusion criteria were analyzed for complications in endoprosthetic reconstructions. The studies highlighted complications such as infection, reoperation rates, and prosthesis survival. Discussion: The study discusses key articles examining complications, emphasizing factors like bone resection, implant fixation types, and tumor characteristics, which influence reoperation rates and prosthesis failure. Despite promising functional outcomes, the risk of complications, particularly infection and mechanical failure, remains significant. Surgical technique, postoperative care, and tumor characteristics are critical in optimizing outcomes. Conclusion: This review identifies key complications in primary extremity tumor endoprosthetic reconstructions, emphasizing the need for long-term follow-up, standardized reporting, and personalized surgical approaches. Further research with homogeneous cohorts is required to enhance understanding and improve patient outcomes.